1998
DOI: 10.1083/jcb.141.6.1335
|View full text |Cite
|
Sign up to set email alerts
|

Specific Single or Double Proline Substitutions in the “Spring-loaded” Coiled-Coil Region of the Influenza Hemagglutinin Impair or Abolish Membrane Fusion Activity

Abstract: We tested the role of the “spring-loaded” conformational change in the fusion mechanism of the influenza hemagglutinin (HA) by assessing the effects of 10 point mutants in the region of high coiled-coil propensity, HA2 54–81. The mutants included proline substitutions at HA2 55, 71, and 80, as well as a double proline substitution at residues 55 and 71. Mutants were expressed in COS or 293T cells and assayed for cell surface expression and structural features as well as for their ability to change conformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
83
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 59 publications
(135 reference statements)
5
83
1
Order By: Relevance
“…We previously showed that a mutant containing proline at residue 55 of the B loop was impaired for fusion, and mutant V55P/S71P, with two B-loop mutations, displayed no fusion (21). Although these findings supported the importance of the spring-loaded conformational change, our prior study did not directly address coiled-coil formation and did not analyze critical conformational changes in HA2.…”
mentioning
confidence: 48%
“…We previously showed that a mutant containing proline at residue 55 of the B loop was impaired for fusion, and mutant V55P/S71P, with two B-loop mutations, displayed no fusion (21). Although these findings supported the importance of the spring-loaded conformational change, our prior study did not directly address coiled-coil formation and did not analyze critical conformational changes in HA2.…”
mentioning
confidence: 48%
“…The HA-mediated fusion is triggered by the acidic pH milieu of the endosomal lumen, which causes the HA ectodomain to convert into a fusogenic conformation. An extended trimeric coiled coil in the HA2 subunit is formed (5)(6)(7)(8). The reconstruction of the three-dimensional structure of the complete HA ectodomain revealed that the preserved trimeric shape of the ectodomain may direct the orientation of the coiled coil with the fusion peptides at its tip toward the target membrane (9).…”
mentioning
confidence: 99%
“…The first characterized of these are hemagglutinin (HA) of influenza virus (34) and gp41 of HIV (22). When these viruses bind to the cell, HA at low pH of an endosome or gp41 at neutral pH undergo detectable conformational changes that eventually involve the coiled coils.…”
mentioning
confidence: 99%
“…Mutagenesis of apolar residues that are positioned to form a hydrophobic core in the ␣-helix of the heptad repeat (25,26) have been shown to alter ␣-helix conformation. Point mutations for influenza, human immunodeficiency virus (HIV) gp41 or other viral proteins alter ␣-helix formation and disrupt viral-induced membrane fusion (1,4,5,10,15,34,43). They have been identified as functional features in some cellular and viral fusion proteins (6,40).…”
mentioning
confidence: 99%